Measuring the long-term success of small-scale marine protected areas in a Philippine reef fishery - Bayley, Daniel T. I.; Purvis, Andy; Nellas, Angelie C.; Arias, Myrtle; Koldewey, Heather J. (Coral reefs, 2020)
Tropical coral reefs are subject to multiple pressures from both natural and anthropogenic sources. These pressures have caused widespread declines in reef health, resulting in the increased use of spatial management tools such as marine protected areas (MPAs). MPAs have proven generally effective if well designed and enforced, but there are limited long-term studies investigating how the presence of small-scale MPAs affects fish populations and reef communities. Using a 12-year time series, we found that small-scale (10–50 ha) community-managed MPAs along the Danajon Bank of the Philippines preserved average fish biomass within their boundaries over time relative to surrounding fished reefs. Unprotected areas are, however, showing significant long-term biomass decline. MPAs were also found to preserve more key trophic groups and larger-bodied commercially targeted reef fish families. Fish biomass of piscivore, scavenger and invertivore trophic groups inside individual MPAs is, however, still declining at a similar rate as outside. Surprisingly, long-term benthic cover and growth form composition were not significantly affected overall by MPA presence, despite the sporadic use of highly destructive dynamite fishing in this region. Coral cover has remained historically low (21–28%) throughout the study, following widespread bleaching mortality. While management tempered overall abundance declines, we found that irrespective of MPA presence, there was a generalised decline of both large- and small-bodied fish size groups across the study region, most steeply within the 20–30 cm length fish, and a shift towards proportionally higher abundances of small (5–10 cm) fish. This indicates a combination of over-exploitation, inadequate MPA size and coverage for larger fish, and the lingering effects of the 1998 bleaching event. Generalised shifts in body size and trophic structure reported here could lead to future reductions in fishery productivity and stability and will be further exacerbated unless broader fishery regulations and enforcement is instated.